Tahlil and Sholawat during the Celebration of the Birthday of the Prophet Muhammad at the Baitul Muhtaddin Mosque - Iin Musriyani; Tias Nur Aini; Dhea Putri Mujiastutik; Darmadi (Jurnal Multidisiplin Madani, 2023)
One of the religious activities in Islam is the Birthday of the Prophet Muhammad SAW, which is the commemoration of the Birthday of the Prophet Muhammad SAW every 12th of Rabiul Awal in the Hijriyah calendar. Celebration of the Prophet's Birthday is a tradition that developed in Islamic society after the death of the Prophet Muhammad SAW. Islam does not displace the culture that lives in a society where Islam comes to enlighten the people's faith. Celebration of the Birthday of the Prophet Muhammad SAW carried out by Muslims is different, but with the same goal. This study intends to discuss the procedures for celebrating the birthday of the Prophet Muhammad SAW at the Baitul Muhtaddin Mosque, such as tahlil and recitation of the prophet's narrations/sholawat. Information about the celebration of the Prophet's Birthday through qualitative research methods, namely descriptive data collection in the form of written words or spoken words of the people observed, language, and pictures. From the research conducted, it will explain the tahlil and narrations of the prophet/sholawat. Finally, this study will provide an overview of the procedures for the Prophet's birthday, namely tahlil and sholawat at the Baitul Muhtaddin Mosque